Research Program: Modeling of Motor Abilities Development and Teaching of Schoolchildren - Olha Ivashchenko (OVS LLC, 2020)
The purpose of this study was to find methodological approaches to the development of a research program in modeling the process of teaching physical exercises, motor abilities development and pedagogical control in schoolchildren's physical education. Materials and methods. The total number of schoolchildren involved in the experiment was: 6-10 years old - 465 (240 boys and 225 girls); 11-13 years old - 430 schoolchildren (205 boys and 225 girls); 14-16 years old - 221 schoolchildren (122 boys and 99 girls). To achieve the purpose set, the following research methods were used: modeling, systems approach, methods of theoretical analysis and generalization; pedagogical testing, methods of recording the respiratory system state, observation and pedagogical experiment; methods of mathematical analysis (logistic and asymptotic functions); mathematical methods of planning multifactorial experiments. Factor, discriminant, and regression analyses were performed. Results. The research program of modeling schoolchildren's physical education includes the development of factor, discriminant, and regression models to obtain new information for planning and managing the processes of teaching physical exercises, motor abilities development, and pedagogical control in schoolchildren's physical education. Conclusions. Modeling is an effective tool for studying the regularities of motor training and for developing physical education programs for children and adolescents. In the program of modeling schoolchildren's physical education, initial data, study object, research methods must meet the following conditions: parametrical description (formulation of tasks, consideration of physical components, analysis of coefficients); initial data (information potential, reliability, accuracy, quantity); methods (similarity, accuracy, implementation time, coincidence with control criteria).